FOREIGN EXPERIENCE OF ECONOMETRIC MODELING OF A CLUSTER MANAGEMENT SYSTEM USING A SINGLE ID SYSTEM IN THE INNOVATIVE DEVELOPMENT OF HOUSING AND COMMUNAL SERVICES. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
According to the practice of developed countries in the world, increasing resource efficiency in housing and communal services and providing housing significantly affect the development of the utility sector and, on this basis, increasing the quality of life of the population, which requires the development of an innovative approach in housing and communal services.